2016
DOI: 10.1111/joic.12314
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Contrast Echocardiography and Clinical Follow‐Up after Percutaneous Closure of Patent Foramen Ovale Using Two Different Atrial Septal Occluder Devices

Abstract: Percutaneous PFO closure was associated with a remarkably low risk of recurrent embolic neurological events, and no long-term device-related major complications. No statistically significant difference emerged between the 2 different SODs regarding BTTE positivity. Long-term follow-up showed that the recurrence of neurological events has been significantly higher in the group treated in a conservative way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…PFO closure carries few drawbacks. One is the persistence of shunt on follow-up control with the potential risk for recurrent thromboembolic events [9]. In the present study, a residual shunt was observed in 16% of patients at one month, which is very similar to other publications [4,10,11].…”
Section: Pfo Closure Drawbackssupporting
confidence: 91%
See 3 more Smart Citations
“…PFO closure carries few drawbacks. One is the persistence of shunt on follow-up control with the potential risk for recurrent thromboembolic events [9]. In the present study, a residual shunt was observed in 16% of patients at one month, which is very similar to other publications [4,10,11].…”
Section: Pfo Closure Drawbackssupporting
confidence: 91%
“…Longer monitoring ideally for at least 72 H should be recommended. The incidence of AF/Flutter, 4.6% in our population, has been reported between 0.4-6.6% [1][2][3][4]6,7,9,[11][12][13][14][15][16][17][18]. Trabattoni has mentioned more supraventricular arrhythmias with Amplatzer versus Figulla but difference was not significant concerning paroxysmal AF [16], as similarly noted in the present study.…”
Section: Pfo Closure Drawbackssupporting
confidence: 75%
See 2 more Smart Citations
“…To validate cohort and case-control studies, the New Ottawa Scale [6] was applied. Six studies were considered of high quality (1 study 8 out 9 points [12]; 5 studies 9 out 9 points [13][14][15][16][17]). We considered the three studies conducted without a control group [18][19][20], with quality acceptable to the study design.…”
Section: Second Systematic Review: Apomentioning
confidence: 99%